African Female Entrepreneurship Merging Profit and Social Motives for the Greater Good - Boateng, Amanobea (Springer International Publishing, 2018)
'This is a welcome contribution to the growing body of research on African entrepreneurship. Its focus on African women entrepreneurs and their unique ability to merge profit and social motives showcases the innate strength, courage and dynamism of our women, and reinforces the pivotal role that they are playing in shaping the Continent's bright future.' -Ndidi Okonkwo Nwuneli, Founder of LEAP Africa, Co-Founder of AACE Foods and Sahel Capital, and Author of Social Innovation in Africa: A Practical Guide for Scaling Impact. 'Amanobea Boateng provides a truly thought-provoking book.' -Dr. Valerie Sabatier, Grenoble Ecole de Management Contributing to academic discussions on entrepreneurship and gender in Africa, this book provides coverage of recent trends and an exploration of the evolution of female entrepreneurship over time. This innovative new text, written from an African woman's perspective, fills a gap in current literature on this topic and places important focus on the role of female entrepreneurship in Africa's development as a continent. Focussing on key issues such as social feminism and the capability approach, the author addresses the possibility of a potential overlap between social entrepreneurship and female entrepreneurship in Africa. Insightful accounts of women from countries such as South Africa, Namibia and Ghana, along with theoretical research into the further development and advancement of female entrepreneurs, make this book an important must-read for those interested in entrepreneurship and gender in Africa.